2018
DOI: 10.1371/journal.pone.0194379
|View full text |Cite
|
Sign up to set email alerts
|

Low serum sodium levels at hospital admission: Outcomes among 2.3 million hospitalized patients

Abstract: BackgroundHyponatremia is the most common electrolyte disorder among hospitalized patients. Controversies still exist over the relationship between hyponatremia and outcomes of hospitalized patients.MethodsTo analyze the association of low serum sodium levels at hospital admission with in-hospital mortality and patient disposition and to compare the distribution of the risk of death associated with hyponatremia across the lifespan of hospitalized patients, we conducted an observational study of 2.3 million pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 34 publications
4
39
1
1
Order By: Relevance
“…In our study, the prevalence of hyponatremia in patients admitted for AECOPD is 10.8% higher than that of patients with community-acquired pneumonia as reported by Cuesta et al [1], but lower than that of patients hospitalized for different causes, including AECOPD [2][3][4]23,24]. In addition to the low prevalence of hyponatremia, the absence of moderate and severe cases also seems noteworthy, despite the high percentage of patients with risk factors to develop it (heart failure, chronic kidney disease, cancer, and certain treatments).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In our study, the prevalence of hyponatremia in patients admitted for AECOPD is 10.8% higher than that of patients with community-acquired pneumonia as reported by Cuesta et al [1], but lower than that of patients hospitalized for different causes, including AECOPD [2][3][4]23,24]. In addition to the low prevalence of hyponatremia, the absence of moderate and severe cases also seems noteworthy, despite the high percentage of patients with risk factors to develop it (heart failure, chronic kidney disease, cancer, and certain treatments).…”
Section: Discussioncontrasting
confidence: 57%
“…Chalela et al associate hyponatremia with longer hospital stay and higher hospital mortality in patients admitted for AECOPD [2]. Al Mawed et al report that hyponatremia is independently associated with hospital mortality and increase in dependence or need for care after discharge, regardless of the diagnosis leading to admission, including AECOPD [24]. The risk of readmission within the first 30 days after discharge due to an episode of heart failure was significantly higher in patients with persistent hyponatremia, regardless of the heart failure severity [30].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that those that stayed in less than 7 days had the lowest prevalence of hyponatremia compared to those that stayed beyond POD 28. There was a positive correlation between the duration of hospital stay and mortality and this is similar to findings by et al [41]. Hyponatremia is an oxidative stress or state and disrupt the oxidation-reduction potential of cells leading to dysfunctional transport pathways particularly the cellular membrane energy requiring glucose phosphorylation needed for building up the energy stores of the body.…”
Section: Discussionsupporting
confidence: 89%
“…3,4 Dysnatremia is the most common electrolyte disorder affecting 14%-25% of all hospitalized patients. [5][6][7][8][9][10] The incidence of dysnatremia may vary in specific populations; for example, it is reported to be lower in non-medical patients and higher in heart failure patients. 11,12 Even though the presence of hyponatremia is more common than hypernatremia, a recent study reported an increase in the incidence of hypernatremia in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…The deviation of serum sodium levels from the normal range, even if the change is minimal, is associated with worse outcomes in hospitalized patients. [5][6][7][8]14 These studies observed the U-shape relationship between serum sodium levels and mortality and suggested that the optimal range of serum sodium was 138-142 mEq/L. 10,12,[14][15][16] Most of the previous studies focused on the impact of admission serum sodium, which is the serum sodium level before interventions during hospitalization.…”
Section: Introductionmentioning
confidence: 99%